Face the Challenge: Adaptation of Shopping Habits in the X Generation a Study of the Happy Fresh Shopping Application - Fransiska, Monica (Riwayat: Educational Journal of History and Humanities, 2023)
The emergence of COVID-19 in Indonesia has become a new challenge for the wider community to adapt to various drastic changes that have occurred suddenly in the social life of the entire community. One of the things that has changed is people's shopping behavior in the midst of this pandemic. People are required to be able to adapt existing technology and change habits that have become their habitus when shopping for basic needs, such as fresh products. Generation X as digital immigrants again experienced the same conditions to adapt to existing technology when shopping for food products, especially fresh products. This study analyzes how the habitus of shopping fresh products for Generation X during the pandemic. Researchers used a qualitative approach with digital ethnographic methods. Data collection is carried out by field observations, online observations, and interviews both offline and online considering the pandemic conditions that require people to limit contact with others. Researchers found that shopping offline is still the first alternative and the habitus of Generation X in fulfil their food needs, especially fresh products. This is evidenced through observations made to informants every time they choose the products, they tend to hold, smell and take the fresh products they want to buy based on their respective valuation preferences of the capital they have. The choice of where to shop is also based on the location closest to where their live and also adjusts to the needs of each informant. Meanwhile, each informant has different preferences regarding the use of online shopping applications, where one of them still uses it more often, while another informant uses online shopping applications only a few times to try it. The final result shows that there is a change in shopping behavior by Generation X which can be seen from the results of observations and interviews with informants, but the habitus of shopping for fresh products by Generation X is still used to shopping offline.